PFM.66 Predictors of outcome in Twin-to-Twin Transfusion Syndrome treated with fetoscopic laser surgery. (9th June 2014) - Muellers, S; Breslin, N; Kent, EM; Malone, FD
Abstract : Aim: To correlate clinical and sonographic parameters with survival following fetoscopic laser ablation for twin-to-twin transfusion syndrome (TTTS). Methods: A retrospective cohort study was performed of all TTTS cases managed with laser in a single fetal therapy centre between 2006 and 2013. Overall survival was correlated with gestational age at diagnosis, placental location, volume of amnioreduction and sonographic features indicating severity of TTTS: Quintero staging and percentage inter-twin growth discordance. Results: Of 64 monochorionic twin pairs treated with selective laser ablation of placental anastamoses the overall survival was 60% (77/128). There was at least one survivor in 73% of cases and dual twin survival in 47%. Two cases were complicated by development of twin anaemia polycythaemia sequence and repeat amniodrainage was required in 3 cases. Mean gestation at diagnosis was 19 +6 weeks (range 16 +0 –24 +5 ) with laser performed at a mean of 20 +2 weeks. 92% were Quintero Stage 2 or 3. Survival was lower in Stage 3 than Stage 2 but this was not statistically significant (67% vs 53%, p = 0.1). No association was found between placental location, gestation at diagnosis, degree of growth discordance or volume of amnioreduction and rates of fetal survival. Conclusion: Fetoscopic laser therapy resulted in survival of at least one fetus for three quarters of affected monochorionic twins. Quintero staging is the only sonographic feature that predicts outcome in these cases.